PKM Peningkatan Literasi Baca-Tulis Siswa MI Al-Islamiyah Melalui Student Centered Learning dan Learning by Playing - Listrianti, Feriska; Al Sidiq, Rofita Aprilia Putri Mardiana; Firdaus, Syahadatinah; Maratus, Nimas Naila (Al-DYAS, 2025)
Students’ reading and writing literacy skills at MI Al-Islamiyah Karanganyar, Paiton, Probolinggo remain relatively low, with more than 60% of third- and fourth-grade students experiencing difficulties in fluent reading and composing simple sentences. This condition is influenced by the dominance of conventional, less interactive teaching methods and the limited use of engaging learning media. This study aims to improve literacy skills through a Student-Centered Learning approach combined with Learning by Playing in a community service program. The implementation stages included literacy needs assessment, development of modules and learning media, reading–writing training using Shared Reading and Creative Writing methods, implementation of interactive literacy games, and evaluation through pre-tests, post-tests, classroom observation, and teacher interviews. Data were analyzed descriptively, both quantitatively and qualitatively, by comparing literacy test scores before and after the program and interpreting observation results of student participation. The findings indicate significant improvement: fluent reading ability increased from 35% to 72%, the ability to write complete sentences rose from 28% to 65%, and active student participation grew from 50% to 85%. In addition, learning motivation improved, as reflected in students’ enthusiasm during literacy games. The study concludes that integrating student-centered methods with educational games is effective in enhancing basic literacy and can be replicated in other madrasahs or elementary schools with similar conditions.